ANALISIS PENILAIAN FINANCIAL DISTRESS MENGGUNAKAN MODEL ALTMAN (Z-SCORE) PADA EMPAT PERUSAHAAN KOSMETIK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Elisia Alza Tuzahri; Aris Munandar (Pusat Riset dan Publikasi, 2022)
This study aims to determine the financial distress assessment of Indonesian cosmetic companies listed on the Indonesia Stock Exchange using the Altman Z-score model. The sample was selected using purposive sampling method. The population in this study is data on the financial statements of four companies in the cosmetic industry listed on the Indonesia Stock Exchange from 2011-2020. This research is a quantitative research using descriptive statistical analysis. Based on the results of data analysis and from the discussion that has been described, it can be concluded that by using the Altman Z-Score method, it is known that cosmetic companies listed on the IDX for the 2016-2020 period are predicted to have the potential to go bankrupt during the year, because the average Z value for cosmetic companies listed on the IDX for the 2016-2020 period is 1.23, meaning that the cosmetic company is in a state of bankruptcy.